Effect of Preliminary Torsional Strain on Low-Cycle Fatigue of Q345B Structural Steel - Hu, X.L.; Liu, Y.J.; Huang, C.X.; Wang, Q.Y. (Проблемы прочности, 2019)
Effect of preliminary torsional strain on low-cycle fatigue of Q345B steel was studied. The specimens were first 0, 180, and 360° twisted, then the low-cycle fatigue of Q345B steel was evaluated in the strain range of 0.3–0.8% by the method of axisymmetrical strain. The cycling response, cyclic stress–strain relationship, strain–life relationship, fatigue life prediction model, and seismic stability at different torsion angles were obtained and analyzed. The strain–life curve is shown to slope down as a power function. The fatigue life comes down with preliminary torsional strain at a constant level. The cycling response varied from cyclic hardening to cyclic softening in preliminary torsion, and the cyclic hardening rate increased linearly with the strain amplitude. The parameters of the Coffin–Manson relation are corroborated with experimental data. After heat treatment, the seismic stability of the material is improved, with torsional strain greatly reducing this characteristic. Electron microscope examination of fatigue fracture revealed a fatigue crack initiating on the surface of the specimen. The propagating crack deviated from its direction, and plasticity of the material dropped as a result of preliminary torsional strain.